Management Placenta Percreta Succesfully With Total Abdominal Hysterectomy. A Case Review : - Rajuddin Rajuddin; Roziana Roziana; Munawar Munawar; Muhammad Iqbal (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2019)
Background: Placenta accreta spectrum is one of the most serious complications of placenta previa and is frequently associated with severe obstetric hemorrhage usually necessitating hysterectomy. The management of placenta accrete spectrum will be discussed here and is essentially the same. The following discussion of management of placenta accreta spectrum applies to all depths of placental invasion. Incidence: In 1950 placentaaccreta was rare, occurring 1 in 30.000 deliveries in the United States. Duringbetween 2008 and 2011 in a cohort of over 115.000 deliveries in 25 hospitals in the United States reaching 1 in 731 deliveries. The marked increase has been attributed to the increasing prevalence of cesarean delivery in recent decades.The incidence of placenta accreta spectrum will also increase due to increasing of caesarean section rate. Case: Mrs.44 yo, G3P2 36-37weekslive, previous cesarean section 2 time,placenta previa totalis, placenta percreta. She’s comes with a chief complaint of lower abdominal cramps, patients regularly antenatal care at obstetrician. Ultrasound finding, a single fetus lives at transvers lie, dorso superior, corresponding to 36-37 weeks, placenta previa, placenta percreta (PAI:83%). This patient planned for elective conservative surgery management, due to cesarean section and or cesarean hysterectomy. Discussion:Surgical conservative management giving birth a baby without a placenta, followed by a hysterectomy, has been shown to reduce the risk of bleeding and the need for blood transfusion. The discovery of placenta accreta spectrum earlier when antenatal care, better birth planning than multidisciplinary science includedfetomaternal, gyneco-oncologist, anesthesiologist, thorac& cardiovascular surgeon, radiology intervention, intensivist - obstetric intensive care, urologist and neonatology can determine the success of handling cases of placenta accreta spectrum so as to reduce maternal, fetal morbidity and mortality. Conclusions:  The discovery of placenta accreta spectrum earlier when antenatal care, planning delivery is better than multidisciplinary science. Management with corporal incisions away from placental implantation, giving birth baby without a placenta, followed by a hysterectomy, has been shown to reduce the risk of bleeding and the need for blood transfusion.